Dynamics of Sequestered Cryptophyte Nuclei in Mesodinium rubrum during Starvation and Refeeding - Kim, Miran; Drumm, Kirstine; Daugbjerg, Niels; Hansen, Per J. (Frontiers in Microbiology, 2017)
The marine mixotrophic ciliate Mesodinium rubrum is known to acquire chloroplasts, mitochondria, nucleomorphs, and nucleus from its cryptophyte prey, particularly from species in the genera, Geminigera and Teleaulax. The sequestered prey nucleus and chloroplasts are considered to support photosynthesis of M. rubrum. In addition, recent studies have shown enlargement of the retained prey nucleus in starved M. rubrum and have inferred that enlargement results from the fusion of ingested prey nuclei. Thus far, however, little is known about the mechanism underlying the enlargement of the prey nucleus in M. rubrum. Here, we conducted starvation and refeeding studies to monitor the fate of prey nuclei acquired by M. rubrum when feeding on Teleaulax amphioxeia and to explore the influence of the retained prey nucleus on photosynthesis of M. rubrum. Results indicate that enlargement of the prey nucleus does not result from fusion of nuclei. Furthermore, the enlarged prey nucleus does not appear to divide during cell division of M. rubrum. The presence of a prey nucleus significantly affected photosynthetic performance of M. rubrum, while the number of retained chloroplasts had little influence on rate of carbon fixation. We interpret results within the context of a model that considers the dynamics of ingested prey nuclei during division of M. rubrum